Dysprosium Oxide-Supported CaO for Thermochemical Energy Storage - Fedunik-Hofman, Larissa; Bayon, Alicia; Gao, Xiang; Tricoli, Antonio; Donne, Scott W. (Frontiers in Materials, 2021)
A novel CaO-based material supported with Ca3Al2O6 and Dy2O3 was found to show excellent performance as a thermochemical energy storage material for use in solar thermal power plants. It retains a carbonation conversion capacity of 82.7% for a period of 40 cycles, as well as exothermic heats of reaction of 582.2 kJ/kg, up to 7 times greater than other materials found in the literature. The improved performance was attributed to the greater prevention of sintering and retention of high surface area by the addition of two inert supports: Ca3Al2O6 and Dy2O3. Long-term effectiveness of the novel material was also evaluated by using a sintering model. It retains an energy storage density of 6.2 kg/kWh after 30 years of cycling, while commercial limestone would require 81 tonnes/kWh equivalent. Limestone requires replacement every 6 thermal cycles, making it impractical for real thermochemical energy storage implementation. The extra cost associated with the addition of supports in this CaO-based material is justified by the long-term durability, which would imply a reduction in the overall capital and operational expenditure of the plant.